Beyond Networks and Trust: A Post-Structuralist Reading of Social Capital, Governance, and Inequality in Southeast Asia - Rivai Mana; Aspin Nur Arifin Rivai (ETNOSIA : Jurnal Etnografi Indonesia, 2026)
On a fundamental level, the conceptualization of social capital has been developed by various prominent thinkers. While previous studies have mainly discussed social capital through networks, trust, participation, and institutional access, This article offers a different reading by treating it as a classificatory discourse that ranks social relations and shapes how community life is recognized in development. It examines the concept of social capital in Southeast Asian development discourse. The objective is to reconsider social capital as a concept that not only describes cooperation, but also influences how development understands community, inequality, and institutional access. The study uses a qualitative and interpretive method based on critical document analysis. It reads theoretical works on social capital, critical development literature, and studies on Southeast Asian development through a post-structuralist approach. The analysis is organized around three themes: social capital as a governing vocabulary, the hierarchy of bonding, bridging, and linking ties, and the marginalization of informal and vernacular practices. The findings show that social capital became influential because it offered a practical language for participation, trust, and community-based development. However, this language can also recast structural inequality as weak community capacity. In Southeast Asia, kinship, religious mutual aid, migrant networks, adat authority, patronage, and informal welfare are often less valued when they do not fit formal development categories. The article argues for a more critical sociology of social capital that places networks within power, recognition, and inequality,